Peningkatan Keterampilan Kewirausahaan melalui Pelatihan Pemasaran Digital Produk Daur Ulang di SMA Santo Yoseph Cakung, Jakarta Timur - Donant Alananto Iskandar; Ignatius Ario Sumbogo; Maulana Malik Muhammad; Anjar Dwi Astono; Boas Nathanael Evelinus; Fathan Silmi Raihan; Andhika Putra Nugraha; Audrey Augustine Suprianto; Jasinta Octora; Striwicessa Senjaya (LPMP Imperium, 2025)
Digital marketing is a promotional strategy using digital media that significantly enhances students’ entrepreneurial skills. A lack of practical skills, including product marketing, often causes high unemployment among high school graduates. This training aimed to equip students of SMA Santo Yoseph, Cakung, East Jakarta, with knowledge and skills in digital marketing. The method used was a participatory training approach, beginning with initial observation and coordination with the school, then the material presentation and hands-on practice. Students were divided into groups to create social media accounts, design promotional content, and upload recycled products to digital platforms. Facilitators provided technical guidance throughout the practical sessions. The activity concluded with evaluation and discussion sessions to assess students’ understanding and the impact of the training. Previously, students had learned how to transform used materials into finished products but could not market them. Through this training, it is expected that students will develop an entrepreneurial spirit and be able to utilize digital media as a marketing tool.